1995
DOI: 10.1007/bf01102890
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A and aflatoxins in breast milk samples from Sierra Leone

Abstract: Breast milk from 113 mothers in two 'Under-Five Clinics' in the Southern Province of Sierra Leone, namely, Njala and Bo, were examined for their mycotoxin content. Only 10 were mycotoxin-free. Eighty-eight per cent of samples contained various aflatoxins and 35% contained ochratoxin A (OTA). Few samples (15%) had a single mycotoxin. Thirty-six (32%) had two mycotoxins and 50 (40%) had three or more. The occurrence of OTA in combination with various aflatoxins was recorded. It is concluded that infants in Sierr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 17 publications
1
46
3
Order By: Relevance
“…From 85 to 100 % of children in African countries have either detectable levels of serum AF-alb or urinary aflatoxins (Gong et al 2002;Gong et al 2003;Gong et al 2004;Polychronaki et al 2008;Turner et al 2000;Turner et al 2003;Turner et al 2007;Wild et al 1990;Wild et al 1993). Several studies have also found AFB 1 and AFM 1 in excreted breast milk samples (Afshar et al 2013;El-Tras et al 2011;Gürbay et al 2010;Jonsyn et al 1995b;Polychronaki et al 2006;Polychronaki et al 2007;Sadeghi et al 2009;Tchana et al 2010).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 96%
“…From 85 to 100 % of children in African countries have either detectable levels of serum AF-alb or urinary aflatoxins (Gong et al 2002;Gong et al 2003;Gong et al 2004;Polychronaki et al 2008;Turner et al 2000;Turner et al 2003;Turner et al 2007;Wild et al 1990;Wild et al 1993). Several studies have also found AFB 1 and AFM 1 in excreted breast milk samples (Afshar et al 2013;El-Tras et al 2011;Gürbay et al 2010;Jonsyn et al 1995b;Polychronaki et al 2006;Polychronaki et al 2007;Sadeghi et al 2009;Tchana et al 2010).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 96%
“…Two out of 100 samples of human milk in Victoria, Australia, contained OTA (3 and 3.6 ng ml À1 ); however, the detection limit of 1.6 ng ml À1 was rather high in this study (Apostolou et al 1998). In Sierra Leone, incidence of OTA in human milk was high (35/40) with positive samples in the range 0.2-337 ng ml À1 and frequent co-occurrence with aflatoxins (Jonsyn et al 1995b); a second study reporting human milk analyses found 30% contamination with OTA (Jonsyn 1999). Recently, ochratoxin A was detected in 2/50 samples of human milk in Brazil (0.01, 0.02 ng/ml) (Navas et al 2005).…”
mentioning
confidence: 99%
“…In human milk samples highest OA concentrations have been found in Sierra Leone, where thirty-five per cent of the samples contained OA at levels from 200 to 337 000 ng/l OA (detection limit: 200 ng/l) (13). In Italy 20 % of milk samples had OA levels in the range of 100 to 12 000 ng/l (14).…”
mentioning
confidence: 99%
“…Prenatal exposure to OA can occur by transplacental transfer (17). It is reported that the OA concentration in fetal serum is twice the maternal one, indicating a possible active placental transport (16).…”
mentioning
confidence: 99%